Value of collaborative investigation by hospital infection control, public health services and a national reference laboratory during an increase in puerperal sepsis - Irene V. Hoogendijk; Diane de Zwart - Slats; Stefan A. Boers; Boas C.L. van der Putten; Nina M. van Sorge; Bibi D.H. Molenaar; Myrthe M.A. Toorop; Marieke B. Veenhof; Karin Ellen Veldkamp; Adriënne S. van der Schoor; Joffrey van Prehn (Antimicrobial Resistance and Infection Control)
Abstract Background In a Dutch tertiary care hospital, two cases of puerperal sepsis were diagnosed within 16 days in June-July 2022. The subsequent outbreak investigation emphasizes the value of collaboration between hospital infection control, regional public health services (PHS) and a national reference laboratory. The aim was to identify possible causes of this increase to prevent further cases of puerperal sepsis. Methods Hospital infection control identified a group of puerperal sepsis cases clustered within the last year in the hospital, a cluster caused by S. pyogenes emm12.0. The hospital and PHS performed contact tracing of cases and HCW involved, investigating epidemiological links, and screening of HCW. The Netherlands Reference Laboratory for Bacterial Meningitis (NRLBM) identified additional regional cases. Subsequently, whole genome sequencing (WGS) analysis was performed on clinical, HCW and regional S. pyogenes isolates. Results Four maternity ward patients were diagnosed with puerperal sepsis caused by S. pyogenes emm12.0 between April and November 2022. Although no additional epidemiological links were identified, all four cases resided within a 6.6 km radius. WGS analysis showed that the four cases were part of an 11-case cluster. Screening of HCW (n = 197) identified two individuals carrying clonally related S. pyogenes isolates. Conclusions Collaboration between hospital, PHS, and NRLBM resulted in an overview of possible epidemiological links. Centralized collection of iGAS case information and strain typing are critical to place hospital clusters in the context of local epidemiology. An increase in healthcare-associated infections may not necessarily imply in-hospital transmission.